EP291/#607 Validation of multi-gene panel next-generation sequencing for the detection of BRCA mutation in formalin-fixed, paraffin-embedded epithelial ovarian cancer tissues. (4th December 2022) - Kim, Eun Taeg; Jeong, Ha Eun; Yoon, Hyung Joon; Kim, Ki Hyung; Suh, Dong Soo
Abstract : Objectives: The therapeutic effect of poly(ADP-ribose) polymerase inhibitors in patients with epithelial ovarian cancer (EOC) with somatic BRCA mutations is consistent with that observed in patients with germline BRCA mutations, indicating the importance of detecting both germline and somatic BRCA mutations concurrently. We compared the efficacy of multi-gene panel next generation sequencing (NGS) in EOC patients' formalin-fixed, paraffin-embedded (FFPE) tissue to that of conventional Sanger sequencing in blood samples. Methods: This study included 48 patients with EOC, and both blood Sanger sequencing and FFPE tissue NGS were conducted in all of them. Clinical and pathological data were reviewed, including age at diagnosis, histology, and stage. Blood Sanger sequencing was performed using peripheral blood leukocytes. The target regions of 90 cancer-related genes were identified using FFPE tissue. Results: The median age of patients was 56.1 years, with serous carcinoma (n=40, 83.3%) and stage III (n=37, 77.1%) being the most common histology and International Federation of Gynecology and Obstetrics stage, respectively. FFPE tissue NGS identified ten pathogenic variants, including all eight pathogenic variants identified by blood Sanger sequencing as well as two additional pathogenic variants. In addition, FFPE tissue NGS identified 19 variants of uncertain significance (VUS), including all ten VUS identified by blood Sanger sequencing as well as nine additional VUS. Conclusions: The FFPE tissue multi-gene panel NGS had 100% sensitivity for detecting BRCA germline mutations and could detect additional somatic mutations. Furthermore, performing FFPE tissue multi-gene panel NGS followed by blood Sanger sequencing sequentially may help differentiate germline from somatic BRCA mutations for genetic counseling.